Military-Political Strategy in the German Party Debate before and after the ‘’Zeitenwende’’: Trends and Consequences - A. D. Davydov (Сравнительная политика)
The "Zeitenwende" announced by German Chancellor Olaf Scholz in 2022 has seriously altered the German domestic political debate. For the first time since the end of the Cold War, German politicians have begun to put the issue of their own country’s defense capability as one of the central topics of internal political discussion. The changes in the public debate provide a new perspective on the current trends in the political landscape, the changing balance of power and the prioritization of various topics in domestic politics. The author therefore aims to determine the place of the domestic German debate on military-political issues. For this purpose, the first objective of the article is to examine the evolution of the German public discourse around military issues, noting its limitations and marginalization. The second task is to study the development after the announced "Zeitenwende" in 2022, focusing on the deliberate politicization of this issue by the leading German parties, which for the first time in recent decades are forced to search for their own niche in military policy. The latest developments since February 2022 are examined through the prism of key party documents and government decrees, as well as public statements of leading politicians. The author assesses the orientation of key actors and the magnitude of their influence on political processes This approach allows to embed the study in the existing body of publications and adds novelty through the analysis of current documents. As a result, the author illustrates how the German military strategy, having become one of the central themes in contemporary German politics, immediately became a “bargaining chip” in the disputes between the parties.